A new genus and species of treefrog from Medog, southeastern Tibet, China (Anura, Rhacophoridae) - JIANG, Ke (Dongwuxue Yanjiu, 2016)
A new genus and species of threefrog is described from Medog, southeastern Tibet, China based on morphological and phylogenetic data. The new genus can be distinguished from other treefrog genera by the following combination of characters: (1) body size moderate, 45.0 mm in male; (2) snout rounded; (3) canthus rostralis obtuse and raised prominently, forming a ridge from nostril to anterior corner of eyes; (4) web rudimentary on fingers; (5) web moderately developed on toes; (6) phalange "Y" shaped, visible from dorsal side of fingers and toes; (7) skin of dorsal surfaces relatively smooth, scatted with small tubercles; (8) iris with a pale yellow, "X" shaped pattern of pigmentation.